Enterprise resource planning adoption lifecycle: a systematic literature review - Hassan, Marina; A. Jabar, Marzanah; Sidi, Fatimah; Jusoh, Yusmadi Yah; Hassan, Salfarina (Asian Research Publication Network, 2016)
Enterprise Resource Planning (ERP) system is a tool in managing the business management function from operational, tactical and strategic management towards the emergence of Information System (IS). The awareness of ERP technology is slowly develops among industrial and non-industrial people. Needs of having the ERP software is not properly discussed within the organization. Some does not even know why they need ERP in their industry. Few in depths knowledge regarding ERP will bring to failure of ERP adoption. The paper was conducted by following systematic literature review methods. Literature search related to ERP methodology reveal 345 papers. After further reading done, 133 papers were identified as a key paper for the topics chosen. Obtaining details understanding of ERP lifecycle, we identified 19 ERP lifecycle papers from the literature from 2009 to 2015. We do a tabulated table to check on ERP needs, objectives and factors affecting the success of ERP adoption in order to get the expectations usage of ERP. A conceptual model of ERP lifecycle will be developed to understand the stages on how to choose a quality ERP software based on the organization objectives. The paper includes the details stages in ERP adoption lifecycle so that user will know specifically what they need to do before or during implementing ERP software. This paper expected to bring awareness about the ERP model itself and to acknowledge people that ERP model will lead to the successful of ERP adoption in developing their business.